Palladium-catalyzed asymmetric carbene coupling en route to inherently chiral heptagon-containing polyarenes - Huan Zhang; Chuan-Jun Lu; Gao-Hui Cai; Long-Long Xi; Jia Feng; Ren-Rong Liu (Nature Communications, 2024)
Abstract Developing facile and direct synthesis routes for enantioselective construction of cyclic π-conjugated molecules is crucial. However, originate chirality from the distorted structure around heptagon-containing polyarenes is largely overlooked, the enantioselective construction of all-carbon heptagon-containing polyarenes remains a challenge. Herein, we present a highly enantioselective synthesis route for fabricating all carbon heptagon-containing polyarenes via palladium-catalyzed carbene-based cross–coupling of benzyl bromides and N-arylsulfonylhydrazones. A wide range of nonplanar, saddle-shaped tribenzocycloheptene derivatives are efficiently prepared in high yields with excellent enantioselectivities using this approach. In addition, stereochemical stability experiments show that these saddle-shaped tribenzocycloheptene derivatives have high inversion barriers.